2011
DOI: 10.5433/1981-8920.2011v16nesp.p1
|View full text |Cite
|
Sign up to set email alerts
|

Conceitos, Categorias e Organização do Conhecimento

Abstract: ResumoNa contemporaneidade, o estatuto do conhecimento é analisado sob diversas configurações epistemológicas devido à emergência crescente de novas combinações interdisciplinares. Nesse contexto, a circulação e a apropriação social da informação assumem formas que exigem distintas maneiras de organizar informação e conhecimento. Para enfrentar esses desafios, diversos paradigmas sobre as relações entre conhecimento, conceito, categoria e sua operacionalização em linguagens documentárias coexistem na área da O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
2
0
2
Order By: Relevance
“…Há, contudo, relações de equivalência que, ainda que não possam ser tomadas de modo absoluto, referem-se a conceitos mais próximos do conceito de SOC, tais como as que relacionam SOC a "sistemas de organização de conceitos" (Kobashi;Francelin, 2011) ou que destacam seu caráter eminentemente hierárquico (Barité et al, 2010).…”
Section: Comparação De Soc Com Outros Instrumentosunclassified
“…Há, contudo, relações de equivalência que, ainda que não possam ser tomadas de modo absoluto, referem-se a conceitos mais próximos do conceito de SOC, tais como as que relacionam SOC a "sistemas de organização de conceitos" (Kobashi;Francelin, 2011) ou que destacam seu caráter eminentemente hierárquico (Barité et al, 2010).…”
Section: Comparação De Soc Com Outros Instrumentosunclassified
“…(figura 2). De manera que todo proceso categorizador implica la comparación entre las características de las cosas, estableciendo un principio de orden que obedece a un conjunto complejo y dinámico de inferencias (Kobashi y Francelin, 2011).…”
Section: Figura 1 Ejemplo De Conceptos En Los Sistemas Para La Organiunclassified
“…Several studies published after 2010 suggested a greater diversity of approaches (e.g. Kobashi and Francelin, 2011; Marradi, 2012; Derqui, 2014; Hjørland, 2015; Maculan and Lima, 2017). From both periods, we also highlight two papers (Thornley and Gibb, 2009; Guedes and Moura, 2016) whose approach, although related to the study of the concept, is focused on the role of the “meaning” in LIS.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the diversity of approaches and theories that exist in LIS, knowledge organization (KO) and classification (see Hjørland, 2016, 2017a, b, 2018a, b, respectively for their discussion), according to Maculan and Lima (2017), there are two theories that are commonly taken for granted and discussed in the LIS literature on concepts: Dahlberg’s analytical concept theory and Ranganathan’s faceted classification theory. In these two theories we can find, in the words of Kobashi and Francelin (2011, p. 15), “the premises of normative effect for the organization of concepts in information retrieval systems.” In this sense, these two theories have functioned as rationalist epistemological canons for LIS, leading to the establishment of the analytical-synthetic approach as a model (Dahlberg, 1972, 1978).…”
Section: Introductionmentioning
confidence: 99%